Agenda 2030: Survey on Sustainable Development Goals through INVALSI data - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
Agenda 2030 for Sustainable Development is a shared action plan for people, for the planet and for prosperity, adopted in September 2015 by the 193 United Nations (UN) Member States. The guidelines of this journey are summarized by 17 Sustainable Development Goals (SDGs) and the associated 169 Targets approved by the UN, with the shared aim to reach them by 2030. The volume, composed of 7 chapters, discusses 3 of the SDGs: to ensure inclusive and equitable quality education, to achieve gender equality and to reduce economic inequality within and across national borders. The INVALSI database provided a valuable resource to the authors to investigate the characteristics of the Italian school system. We wish the volume reading encourages the discussion about possible ameliorative interventions and it is a starting point to measure potential progress.